PERANCANGAN APLIKASI PENGOLAHAN DATA PENERIMAAN DAN PENGELUARAN KAS PADA PT. PERTAMINA DRILLING SERVICES INDONESIA (PT. PDSI) - Carolina, Falentine; Wijaya, Khana; Suparianto, Rishi (LPPM UNIVERSITAS BINA INSAN, 2025)
PT. Pertamina Drilling Services Indonesia (PT. PDSI) is a company that operates in the oil drilling industry and is located at Jalan Jenderal Sudirman No. 03, Prabumulih, South Sumatra. The company has been using Microsoft Excel to record its cash inflows and outflows. However, this method is still prone to errors in data processing, which makes the financial reports less accurate. This research aims to develop a website-based application to make the cash reporting process easier, more accurate, and more efficient. The method used in this research is descriptive and qualitative, including observation, interviews, and literature study. The data comes from both primary and secondary sources. The application is developed using the Rapid Application Development (RAD) method. System design tools such as use case diagrams, class diagrams, and activity diagrams are used. The application is built using PHP and MySQL. With this application, it is expected that PT. Pertamina Drilling Services Indonesia (PT. PDSI) Rig Operation II can manage its cash data more efficiently, and that the company’s leaders can more easily review the financial information.